1992
DOI: 10.1039/p29920000629
|View full text |Cite
|
Sign up to set email alerts
|

EPR investigation into the kinetics and mechanism of the one-electron reduction of benzenediazonium ions by FeII–EDTA and other iron(II) complexes

Abstract: A n EPR approach has been developed and applied t o the determination of the rate constants for the decomposition of some arenediazonium ions b y Fell complexes to give aryl radicals. In continuousf l o w experiments, steady-state concentrations have been measured both for the aryl radical-adducts to the fumarate anion and for ' CH,CO,-(obtained b y reaction of Ar' with the iodoacetate anion): analysis of the dependence of these upon [Fe"] and [ArN,'] leads to values of the rate constants for electron transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…ESR studies and other theoretical studies have shown that the radical character of phenoxyl radicals is well dispersed in the aromatic ring, giving relatively high stability to the radical 6871. The spin densities obtained from our calculations confirm this radical dispersion.…”
Section: Resultssupporting
confidence: 82%
“…ESR studies and other theoretical studies have shown that the radical character of phenoxyl radicals is well dispersed in the aromatic ring, giving relatively high stability to the radical 6871. The spin densities obtained from our calculations confirm this radical dispersion.…”
Section: Resultssupporting
confidence: 82%
“…copper-free) conditions, Scheme 3 2 PERKIN outer-sphere reductions of diazonium ions by ferrocyanide in aqueous solution and by decamethylferrocene in MeCN have been reported by Doyle and co-workers 22 and we have previously inferred comparable behaviour in their reduction by Fe 2ϩ ligated by EDTA in aqueous solution at pH 9. 23 No kinetic study of Sandmeyer cyanation has been carried out, perhaps because of the formation of the intermediate solid or oily phases which have been reported for the reaction in aqueous solution. 24 Nevertheless, cyanide being a 'pseudohalide', the reaction is believed to occur in a manner comparable to that of the copper() halides and there may well be more than one active cyanocuprate species.…”
mentioning
confidence: 99%
“…Since EDTA is only a hexadentate ligand (two tertiary amines with lone electron pairs and four carboxylic acid groups), iron has two orbitals free to interact with the diazonium ion. Not only this, but EDTA lowers the reduction potential of iron from 0.77 to 0.14 and thereby makes it a better reductant and increases the favorability of reduction of diazonium (Gilbert et al 1992). Thus, EDTA appears to selectively create the interference with NO − 3 and NO − 2 analyses.…”
Section: Mode Of Interferencementioning
confidence: 99%
“…Reducing agents (Vollhardt and Schore 1994). In fact, Gilbert et al (1992) showed that Fe(II)EDTA at pH 9 causes the loss of azide from several very similar benzene diazonium ions. Thus, we hypothesize that Fe(II)EDTA reduces the diazonium ion (see Fig.…”
Section: Mode Of Interferencementioning
confidence: 99%